THE ROLE OF THE COMMUNITY PARTICIPATION IN THE ARCHITECTURAL HERITAGE PROJECTS IN PALESTINE (COMPARATIVE STUDY) - Ziad M. M. Shehada, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
Community participation is very important in the heritage conservation projects. It assists the people to solve their problems and allow them to preserve the legacy for the future generation. The study aims to evaluate the role of community participation in the cultural heritage projects in Palestine using Arnstein's ladder and explore the extent to which such participation contributes to the success of these projects. The researcher adopts an analytical and comparative research method to deeply understand the importance of involving the community in the conservation projects through six case studies: three inside Palestine and three outside Palestine. The study concludes that there is a distinction in the concept of community participation in conservation projects. Besides, community participation takes different forms depending on the stage of works, the request of the stakeholders, and the categories of participants. The article emphasises the necessity of activating and adopting community participation as a method for the implementation of conservation projects.